Let’s Play Huayue!: Learning Traditional Chinese Musical Instruments Through Augmented Reality - Loo, Qiao Li; A Hamid, Rahayu (Applied Information Technology And Computer Science, 2024)
Traditional Chinese musical instruments are a diverse range of instruments that have been used in China for thousands of years as a key component of Chinese music. As Western musical instruments become more prominent in the media and are more frequently exposed on radio and television, today's youth are becoming more interested in them. Besides, there are very few mobile applications regarding traditional Chinese musical instruments currently. Hence, the proposed mobile learning app "Let's Play Huayue!" aims to revitalize interest in traditional Chinese music and its instruments through 3D augmented reality and informative content. Multimedia Mobile Content Development (MMCD) methodology is deployed to develop this application on the Android platform. The application is designed to help users aged 10 and above to learn about traditional Chinese musical instruments without having to physically approach them, as well as build a respect for Chinese culture. The results of user testing demonstrate a greater acceptability level, with an average percentage of 77.75%.